Laparoscopic ultrasonography-guided myomectomy of submucosal myoma for preserving endometrial integrity - Kazuki Saito; Tomonori Ishikawa; Moeko Onose; Rinko Ibi; Kenichi Tatsumi; Naoyuki Miyasaka (Clinical and Experimental Obstetrics & Gynecology)
Background: Submucosal myoma is a common gynecological disease that causes menorrhagia and infertility. While hysteroscopic surgery is a minimally invasive and effective method for treating submucosal myomas, its feasibility depends on the size and location of the myomas. Conversely, abdominal procedures enable enucleation of submucosal myomas and preservation of endometrial integrity, but are accompanied by technical difficulties. Herein we report the case of an infertile woman with a submucosal and an intramural myoma who underwent laparoscopic myomectomy using laparoscopic ultrasonography. Case: The patient was a 36-year-old infertile woman. Transvaginal ultrasonography revealed a 15 mm submucosal myoma with a 60% myometrial extension in the anterior uterine wall and a 49 mm intramural myoma in the posterior wall. During myomectomy, the submucosal myoma was not apparent from the external side of the uterus; therefore, laparoscopic ultrasonography was used to detect it. Under ultrasonography, vasopressin was injected between the myoma and the myometrium, thereby separating the layers. Consequently, we were able to resect both myomas without breaching the endometrium. Conclusions: The present case demonstrates the effectiveness of laparoscopic ultrasonography for detecting submucosal myomas and ensuring injection of vasopressin into the proper layer. These advantages allow surgeons to preserve endometrial integrity during laparoscopic myomectomy.